2022
DOI: 10.1542/peds.2021-056003
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and Duration of Physical Activity and Cardiorespiratory Fitness

Abstract: OBJECTIVES: There is no clear guidance on the intensity and duration of physical activity (PA) that adolescents require to maximise cardiorespiratory fitness (CRF). We aimed to determine the strength of associations between each PA intensity and CRF, independently of other intensities, and the PA duration at each intensity associated with maximal CRF. METHODS: PA and CRF were assessed in 339 adolescents aged 13 to 14 years by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
(76 reference statements)
1
14
0
2
Order By: Relevance
“…From the literature, it has been found that the higher the magnitude of the negative of E ad , the longer the recovery time. 52,53 Hence in this study a higher negative adsorption energy was observed for P@MoS 2 _NH 3 , which shows it could be useful as a sensor material.…”
Section: Resultssupporting
confidence: 59%
“…From the literature, it has been found that the higher the magnitude of the negative of E ad , the longer the recovery time. 52,53 Hence in this study a higher negative adsorption energy was observed for P@MoS 2 _NH 3 , which shows it could be useful as a sensor material.…”
Section: Resultssupporting
confidence: 59%
“…Meanwhile, the hot topic is cardiorespiratory fitness. The results of research conducted by Burden et al (2022) show that adolescents who engage in 20 minutes of vigorous physical activity per day on average have maximal cardiorespiratory fitness, and there is little evidence that engaging in more or less intense physical activity is beneficial. In addition to always being related to physical health and fitness, cardiorespiratory fitness is also related to cognitive function and psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…4 Estes indicadores realçam o declínio da prática de exercício físico nos jovens em geral, realçando-se a exceção dos estudantes do sexo feminino nas escolas secundárias, os quais têm aumentado a participação desportiva, pelo menos até 2015, ano em que foi publicado o estudo de Basett D R e colaboradores. 5 A AFCR é um importante determinante da saúde e, apesar da genética ser importante para a sua definição 6 , ela pode ser melhorada também nas escolas através do exercício físico 7 , o qual é o principal fator modificável. Dobbins M e colaboradores, do Canadá, publicaram uma revisão sistemática sobre a evidência da eficácia de intervenções na escola para a promoção da atividade física e aptidão em crianças e adolescentes (6-18 anos de idade).…”
Section: Palavras-chave / Abstractunclassified
“…Esta informação é muito importante pois é referido na Discussão que a maioria dos adolescentes falha o objetivo de exercício durante 60 minutos com intensidade moderada / alta e o período de 20 minutos é mais fácil de incluir na rotina quotidiana. Também nesta secção, os autores discutem a validade do teste de vaivém como instrumento de avaliação da AFCR, referindo que a avaliação direta do VO 2 máximo seria mais desejável 7 , mas com praticabilidade bastante inferior em população sob estudo tão numerosa.…”
Section: Palavras-chave / Abstractunclassified